Risk Perception Regarding Drug Use in Pregnancy: A Clinical Opinion. Issue 1 (March 2018) - Widnes, S.F.; Schjøtt, J.
Abstract : ( Am J Obstet Gynecol . 2017;216(4):375–378) Both expectant mothers and their doctors have misperceptions about the risks of taking drugs during pregnancy, thinking that every drug represents a dire risk to their unborn child even though maternal drug use accounts for only 1% of birth defects. Sometimes there are important reasons to take a medication during pregnancy for the mother's health and to avoid an adverse effect on the fetus from her untreated condition. The risks of taking a drug must be balanced by the benefits that it provides.